The effect of Modified Radical Mastectomy (MRM) with and without latissimus dorsi flap on seroma of Locally Advanced Breast Cancer (LABC) in Sanglah Hospital - Anak Agung Chris Tedy Pramana; I Ketut Widiana; I Gde Raka Widiana (DiscoverSys Inc., 2021)
Background: Locally Advanced Breast Cancer (LABC) is defined as breast cancer spread locoregionally and without any signs of metastasis. Stage IIIA breast cancer is one type of LABC that can be removed surgically, and Modified Radical Mastectomy (MRM) remains the first surgical option. Seroma production is one of the most common complications post MRM, with the hypothesis stating that the Latissimus Dorsi (LD) flap technique is responsible for resulting in higher seroma output. This study aims to compare seroma production in LABC patients post MRM with and without LD flap.Methods: This prospective cohort study was conducted in Sanglah General Hospital, Denpasar, between November 2018 and January 2020. The study sample was divided into 2 groups: LABC patients post MRM with and without LD flap reconstruction. Seroma was measured in milliliters (ml) and collected from the first to fifth day post-operation. Data were analyzed using SPSS version 21 for Windows.Results: Forty LABC patients were enrolled in this study. The mean age for the group without latissimus dorsi flap was 48.45±7.01 years and 49.40±10.77 years for the group with latissimus dorsi flap. The mean seroma production in LABC patients who underwent MRM without and with LD flap reconstruction was 696.45±66.37 ml and 490.10±62.11 ml. There was a significant difference in the total of seroma between the treatment group without-LD flap and compared to with-LD flap reconstruction (p<0.001).Conclusion: Seroma production is significantly higher in LABC patients post MRM without LD flap reconstruction than LABC patients with LD flap.